A weak interaction between the U2A' protein and U2 snRNA helps to stabilize their complex with the U2B" protein. - Boelens, W (1991)
The U2 snRNP complex contains two specific proteins, U2B" and U2A'. We have analysed the interaction of U2A' with U2B" and with U2 RNA. U2A' can form an weak but detectable RNA-protein complex with U2 RNA and a stable protein complex with U2B". This protein-protein complex binds efficiently and specifically to U2 RNA. Binding experiments with mutant forms of U2A' shows that the region of U2A' essential for binding to U2B" is extensive, being located between amino acid position 1-164. The behaviour of the wild type U2A' protein, and in particular of a mutant version of the protein in which amino acids 3, 4 and 5 are mutated, suggests that U2A' forms a weak interaction with U2 RNA which helps to stabilize the U2A'-U2B"-U2 RNA complex. Mutants of U2 RNA were used to localize the region of U2 RNA important for interaction with U2A'. The results show that U2A' interacts with the stem of hairpin IV.